Modeling the Drivers of Online Purchase Decisions: An Empirical Study of Shopee Users in Indonesia - Hikmah, Ananda Mutiara; Mahmud, Mahmud; Darodjat, Tubagus Achmad (Jurnal Telekomunikasi dan Informatika, 2025)
This study aims to analyze the factors influencing consumer purchasing decisions on the Shopee marketplace. Shopee was chosen as the research object because it is one of the largest e-commerce platforms in Indonesia, rapidly growing through digital marketing strategies, free shipping promotions, and interactivefeatures such as customer reviews and live chat. Given its extensive user base, particularly among university students, it is essential to examine the role of online reviews, trust, ease of use, and service quality in shaping purchasing decisions on Shopee.The research employed a quantitative approach using a Likert -scale questionnaire as the main instrument. Data were collected from 150 student respondents in Semarang who had purchased products from Shopee more than twice, with an age range of 20–23 years. Purposive sampling was applied, and the data were analyzed usingSPSS through validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing (t-test and F-test) to assess the relationships among variables.The findings reveal that all four independent variables—online reviews, trust, ease of use, and service quality—have a positive and significant effect on consumer purchasing decisions on Shopee. Collectively, these variables explained 88.7% of the variance in purchasing decisions, with trust and service quality emerging as the most influential factors. These results emphasize that strengthening consumer trust, ensuring credible online reviews, and enhancing service quality are crucial strategies for Shopee to maintain customer loyalty and improve competitiveness in the e-commerce industry.